Smoking and Alcohol Consumption Behavior Among Male Senior High School Students - Meilani, Niken; Hariadi, Sunarru Samsi; Haryadi, Fransiskus Trisakti (Jurnal Kesehatan Masyarakat, 2024)
Smoking and alcohol consumption behavior prevailed greater among adolescents period. These behavior could cause health risks. About 1 of every 4 adolescents in Indonesia were smokers and 3% of adolescents were drinking alcohol. This study aimed to analyze the association between self-efficacy with smoking and alcohol consumption among adolescents. This was a cross-sectional study carried out in July-September 2022. The study population was high school male students in Yogyakarta. A multistage random sampling technique was employed, involving 163 respondents. The instrument used was a questionnaire that has been tested. Data was analyzed in chi-square. Almost half of males had smoking behavior (39,3%). Males who were smoking started their behavior at the mean age of 15 years old. Most of them had low self-efficacy (70,6%). All male adolescents who had high self-efficacy do not have alcohol drink behavior. There was a relationship between self-efficacy with smoking behavior (p=0,001) and alcohol consumption (p=0,004). Strengthening self-efficacy is essential for adolescents. The government, family, and peers have an important role in increasing self-efficacy